INFLUENCE OF THE QUANTITY OF BENZENE ON THE PERFORMANCE CHARACTERISTICS OF GASOLINE (Euro-Asia Conferences, 2021)
The article shows the influence of the amount of benzene in gasoline on the octane number and performance characteristics of the fuel, as well as toxic substances formed during the combustion and partial combustion of benzene. Described are hydrocarbons that determine the toxicity of commercial gasolines and products of their combustion. The article describes the effect of changes in the benzene content in the composition of gasoline on the octane number of the fuel. Suggestions for simplification of the technological system for standardizing the amount of benzene in gasoline are presented.